Hydrothermal fluid ejector for enhanced heat transfer of a thermoelectric power generator on the seafloor. Issue 17 (3rd August 2021) - Gai, Xiaotao; Wu, Shijun; Yang, Canjun
Abstract : A novel cooling method for the hydrothermal power generator which does not need auxiliary power consumption is proposed. The output power of the thermoelectric generator can be increased by 19.5–32.5%. Abstract : Interest in deep-sea hydrothermal research has been rapidly increasing. Advances in harvesting energy from hydrothermal vents will facilitate long-term seafloor observation systems that do not rely on batteries. A thermoelectric generator can continuously convert hydrothermal heat into electrical energy, but the extreme environment of the deep sea makes heat dissipation a challenge. To address this issue, we developed the hydrothermal fluid ejector, which is a novel cooling structure with no moving parts that can change the cold-side heat transfer from natural convection to forced convection. By combining a thermoelectric generator with the ejector structure, we can utilize the kinetic energy of a vent flow instead of a pump-driven cooling system to drive cold water. This cooling method is highly reliable and requires no auxiliary power. An experiment was conducted with a scaled model and particle image velocimetry to validate the water driving capability of the ejector, and a laboratory experiment was conducted to validate the cooling method. The experimental data were consistent with simulation results using computational fluid dynamics. The experimental results indicated that the ejector could improve the thermoelectric generator output power by 19.5–32.5%. Thus, the proposed structure can facilitate practical and maintenance-free cooling for deep-sea thermoelectric generator systems.